Employee Appraisals and Cognitive Information Processing Systems - Ahmad, Rusli (Universiti Malaysia Sarawak, 2008)
This book is vitally important because performance activities is become one of the main task for officer or manager in every organization. In every organization, human beings or workers play vital role in determining its survival. Human capital, or workers, have become the ultimate assets compared with other resources (money, land , machine, factory, hardware, software, material, equipment and etc). and are the key or prerequisite factors in making the operation of the organization or factory runs as planned. Linking the appraisal system to the reward system means that it can be used as a strategic tool by organizations to achieve their mission and vission.